A retrospective analysis comparing set up errors from standard versus customised headrests for head and neck radiotherapy. Issue 3 (August 2022) - Anderson, E.; Pilling, K.; Iqbal, S.; Pearson, R.L.
Abstract: Introduction: In response to advice from The National Institute for Health and Care Excellence (1) to reduce hospital visits during COVID-19, standard headrests were introduced for head and neck radiotherapy within Northern Centre for Cancer Care (NCCC). The standard headrest requires one mould room appointment compared to 3 appointments with customised headrests. Methods: Two groups of 10 patients treated between December 2019 and June 2020 were retrospectively analysed by 1 observer. Groups were stratified according to age, sex and tumour site. One group had customised headrest and the other had standard headrest. Five hundred and forty seven cone beam computed tomography images were reviewed. A 6 Degree of Freedom match was performed then chin, shoulder and spine position were assessed using dosimetrist drawn structures. Structures out of the tolerance were recorded. A chi-squared test was used for statistical analysis. Results: The out of tolerance chin position count recorded was 21 for customised headrest and 36 for standard headrest, p-value 0.046. The shoulder position count was 13 for customised headrest and 77 for standard headrest p-value <0.001. The spine position count was 3 for CHR and 21 for standard headrest, p-value <0.001. This means the headrests compared are not equivalent in terms of set up reproducibility. Overall the standard headrest group had 10 set-up re-scans and no set up re-scans were recorded in the customised headrest group. Conclusion: Fewer hospital visits with SHR reduce patient exposure to COVID-19. However, CHR provided a more reliable level of immobilisation in this study. Implications for practice: The radiotherapy service will be reviewed in line with these findings.